SUSTENTABILIDADE SOCIAL NA PRODUÇÃO DE FRANGO DE CORTE - SOUZA, Sulma Vanessa; ALMEIDA, Marcel Gonçalves de; OLIVEIRA, Luanne Escobar do Nascimento; ANDRADE, Bruno Neto de; SABBAG, Omar Jorge (ANAIS DO ENIC, 2020)
-